Artificial light and biting flies: the parallel development of attractive light traps and unattractive domestic lights - Wilson, Roksana (Parasit Vectors, 2021)
Light trapping is an important tool for monitoring insect populations. This is especially true for biting Diptera, where light traps play a crucial role in disease surveillance by tracking the presence and abundance of vector species. Physiological and behavioural data have been instrumental in identifying factors that influence dipteran phototaxis and have spurred the development of more effective light traps. However, the development of less attractive domestic lights has received comparatively little interest but could be important for reducing interactions between humans and vector insects, with consequences for reducing disease transmission. Here, we discuss how dipteran eyes respond to light and the factors influencing positive phototaxis, and conclude by identifying key areas for further research. In addition, we include a synthesis of attractive and unattractive wavelengths for a number of vector species. A more comprehensive understanding of how Diptera perceive and respond to light would allow for more efficient vector sampling as well as potentially limiting the risk posed by domestic lighting. [Image: see text]